Activin‐βc reduces reproductive tumour progression and abolishes cancer‐associated cachexia in inhibin‐deficient mice. Issue 4 (25th January 2013) - Gold, Elspeth; Marino, Francesco Elia; Harrison, Craig; Makanji, Yogeshwar; Risbridger, Gail
Abstract: Activins are involved in the regulation of a diverse range of physiological processes including development, reproduction, and fertility, and have been implicated in the progression of cancers. Bioactivity is regulated by the inhibin α‐subunit and by an activin‐binding protein, follistatin. The activin‐βC subunit was not considered functionally significant in this regard due to an absence of phenotype in knockout mice. However, activin‐βC forms heterodimers with activin‐βA and activin‐C antagonizes activin‐A in vitro . Thus, it is proposed that overexpression, rather than loss of activin‐βC, regulates activin‐A bioactivity. In order to prove biological efficacy, inhibin α‐subunit knockout mice (α‐KO) were crossed with mice overexpressing activin‐βC (ActC++). Deletion of inhibin leads to Sertoli and granulosa cell tumours, increased activin‐A, and cancer‐associated cachexia. Therefore, cachexia and reproductive tumour development should be modulated in α‐KO/ActC++ mice, where excessive activin‐A is the underlying cause. Accordingly, a reduction in activin‐A, no significant weight loss, and reduced incidence of reproductive tumours were evident in α‐KO/ActC++ mice. Overexpression of activin‐βC antagonized the activin signalling cascade; thus, the tumourigenic effects of activin‐A were abrogated. This study provides proof of the biological relevance of activin‐βC . Being a regulator of activin‐A, it is able to abolish cachexia and modulate reproductive tumour development in α‐KO mice.